Pierwszy List Jana jako świadectwo teologiczne o historii zbawienia realizującej się w Jezusie Chrystusie - Kot, Piotr (Verbum Vitae, 2015)
Reading the First Letter of John, one is led to inquire about the nature of the testimony that the author of the letter offers to the Christian community in crisis. Is this a testimony based on an inculcated doctrine or does it originate in the historical experience of the author? This is, in fact, a question regarding the authority of the teaching presented in the letter. Vocabulary employed in the letter, particularly in its prologue, permits one to define the testimony under consideration as a theological testimony. It does not consist in a faithful recalling of memories of past historical events only. After all, the author of 1 John does not refer directly to any words or deeds of an earthly Jesus. Rather, the testimony consists in treating the historical facts as a “source of the present time.” This testimony enjoys strong authority because it arises from two sources: from an account of the eye-witness of the paschal life of Jesus Christ and from the reflection on the existential outcomes of this historical and salvific event in relation to the current needs of the community.